EFEKTIFITAS PEMBELAJARAN GERAK DASAR LOMPAT MELALUI MODIFIKASI ALAT - Bahrun Bahrun; mashud masuh (Lambung Mangkurat University, 2014)
The effectiveness of learning basic movement jump through modification tool learners class V SDN Pandulangan I District of central Tapin regency of Tapin. Purpose of reseach this is to increase the effectiveness of learning basic movement jump on learners class V SDN Pandulangan I. The subject of research is the learners class V SDN Pandulangan I totalling 20 people comprising 13 men and 7 learners learner's daughter. The methods used in this research is a method of action class (PTK).Results of the study revealed that, in the initial observations of 20 learners there are only 4 people who meet the ketuntasan study on motion learning basic jump. After teridenfikasi some causes of the problem then compiled the planning of learning that are applied or applied at the cycle I and cycle II. On first cycle there were 14 people who are having the learners ketuntasan his studies. After going through the stage of the class action research ranging from planning, implementation, observation and reflection on the cycle I, then the cycle II contained 19 people who are having the learners learning complete. This indicates that the action is given by the teacher/researchers that learning through modification tools give a positive impact on learning outcomes for learners. The existence of positive impact of improved learning outcomes learner, then it can be said the research class action is successful. Keywords: Effectiveness, learning basic jump motion, modification tools.